2020
DOI: 10.1111/bjd.19309
|View full text |Cite
|
Sign up to set email alerts
|

Complete response of metastatic pleomorphic dermal sarcoma to anti‐PD‐1 therapy

Abstract: DEAR EDITOR, An 87-year-old gentleman presented with a scalp nodule. A subsequent biopsy (a) demonstrated pleomorphic dermal sarcoma (PDS). The patient underwent an excision and received adjuvant radiotherapy. He presented 4 months later with two new scalp lesions and an enlarged left parotid gland. A biopsy confirmed metastatic PDS that was heavily infiltrated by T lymphocytes (b). A staging positron emission tomography (PET) scan demonstrated two lung metastases. The patient commenced treatment with the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…pembrolizumab, nivolumab) or the anti–CTLA-4 antibody (ipilimumab), or a combination of these agents was presumed in reference to other highly mutated and immunogenic tumors including other skin tumors such as malignant melanoma and cSCC ( 18 , 32 , 33 ). In the meantime, the exceptionally high efficacy of the anti-PD-1 inhibitor pembrolizumab has been described in case reports or small case series (see Table 1 ) ( 2 , 15 17 ). Until now, there are no case reports describing the use of other CPI in PDS patients.…”
Section: Treatment Of Advanced Stage Pds Including Immune Checkpoint ...mentioning
confidence: 98%
See 1 more Smart Citation
“…pembrolizumab, nivolumab) or the anti–CTLA-4 antibody (ipilimumab), or a combination of these agents was presumed in reference to other highly mutated and immunogenic tumors including other skin tumors such as malignant melanoma and cSCC ( 18 , 32 , 33 ). In the meantime, the exceptionally high efficacy of the anti-PD-1 inhibitor pembrolizumab has been described in case reports or small case series (see Table 1 ) ( 2 , 15 17 ). Until now, there are no case reports describing the use of other CPI in PDS patients.…”
Section: Treatment Of Advanced Stage Pds Including Immune Checkpoint ...mentioning
confidence: 98%
“…In the last years, it could be shown that PDS are inflammatory and immunogenic tumors with a very high mutational burden. Experimental data and clinical reports indicate that PD-1/PD-L1-blocking antibodies are highly effective in patients with unresectable or metastatic PDS and suggest its use as first line treatment in these advanced tumor stages ( 2 , 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cases with high numbers of TIL and expression of PD-L1 or other checkpoint molecules, off-label treatment with a checkpoint inhibitor such as an anti-PD-1 antibody may be considered, provided that the reimbursement situation has been clarified. There are some case reports that PD-1/PD-L1 inhibiting antibodies may be effective [18,43,44,58].…”
Section: Medical Therapymentioning
confidence: 99%
“…Im Falle einer hohen Zahl an TIL als auch Expression von PD-L1 oder weiterer Checkpoint-Moleküle, kann eine Off-Label-Therapie mit einem Checkpoint-Inhibitor wie einem Anti-PD-1-Antikörper nach entsprechender Klärung der Kostenübernahme erwogen werden, zumal in Fallberichten eine Wirksamkeit von PD-1/PD-L1-blockierenden Antikörpern beschrieben wurde [18,43,44,58].…”
Section: Medikamentöse Therapieunclassified